UPAYA TOKOH AGAMA DALAM PELAKSANAAN WALIMATUL ‘URSY AGAR SESUAI DENGAN AJARAN ISLAM DI DESA TEBAT MONOK KECAMATAN KEPAHIANG KABUPATEN KEPAHIANG - Akbar, Ali (QIYAS: JURNAL HUKUM ISLAM DAN PERADILAN, 2018)
The  formulation  of  this  study  is:  First,  how  the  position   of  religious leaders in the community of Tebat Village Monok? Secondly,  what is the efforts of religious leaders  in the cultivation  of religious values at the wedding  party (Walimah al-’Ursy) in Tebat  Monok village Kepahiang district? This type of research  is descriptive  research  with sociological juridical ap- proach.Data collection  uses interviews,  observations and  documentation. This research  concludes  that:  First, the position  of religious leaders  in the Village  Tebat   Monok  Kepahiang  District  is  a  leader   of  religious  worship activities, train people  in religious practice  and  become a community advisor..  Secondly,  the efforts made  by religious leaders  in Tebat  Monok Village are: Establish a da’wah  approach by giving an enlightenment to the public on various occasions  such as in a lecture or gather- ing of citizens on how to implement  walimahan by paying close attention to the aspects  of religious teaching,  using a personal approach to Community by giving advice and  feedback  about  how it should  be done  so that the party is not redundant, does not cause  vice and benefit to the people  but still has the meaning for those who wish